Reproductive health practices of rural mothers in Bangladesh: Community-based learning experiences for medical students (South East Asia Journal of Public Health, 2015)
Reproductive health is an emerging issue in Bangladesh as well as in the world. This was a survey conducted among rural women of the reproductive age group as a part of academic exposure of the medical students in community medicine during the Residential Field Site Training (RFST) program. The study aimed to determine antenatal and natal services, nature of complications during last delivery, and health problems related to the reproductive tract. The study also highlighted the views of the students in various aspects of the RFST program during development and implementation. A descriptive cross-sectional study was carried among 534 married women of reproductive age during December 2012 in different villages of Dhamrai Upazila, Dhaka. Medical students collected the data using a pre-tested questionnaire through face to face interview. The students feedback was collected through another questionnaire using Likert 5-points scale. The study revealed that the mean age of respondents was 29±7.3 years, 86% were housewives, 58% had 2-4 children and mean age of the respondents at first issue was 19±3.5 years. The study showed that 75.7% and 75.4% respondents received antenatal visits and TT immunization respectively. Among the respondents 48% had hospital delivery and 52% had home delivery, of which 30% were by skilled and 22% were by untrained birth attendants. The common reproductive health problems in relation to delivery were obstructed labor (28%), PPH (22%) and abortion (21%.) Other related reproductive health problems included: menstrual disturbance (52%), leucorrhoea (41%) and UTI (35%). In this study, students expressed their satisfaction about the RFST program except duration of program. Medical students should provide opportunities to learn about reproductive health in a community-based setting which helped to increase their skills and confidence.DOI: http://dx.doi.org/10.3329/seajph.v4i1.21844 South East Asia Journal of Public Health Vol.4(1) 2014: 63-66